2019
DOI: 10.1097/mpg.0000000000002168
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Donkey Milk–derived Human Milk Fortifier in Feeding Preterm Infants

Abstract: Objectives:The purpose of the present randomized controlled clinical trial was to compare the use of donkey milk–derived fortifier (DF) with commercial bovine milk–derived fortifier (BF) in very preterm or very-low-birth-weight newborns, in terms of feeding tolerance.Methods:This trial included 156 newborns born at <32 weeks of gestational age and/or with a birth weight ≤1500 g. Newborns were randomized 1:1 to receive enteral feeding with either a BF-arm, or a new, DF-arm for 21 days. The fortification protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…Table 2 reports the main clinical outcomes following ADJ fortification in the two groups. The relative risk (RR) ratio for the primary outcome of the original clinical study [18], i.e., the occurrence of at least one feeding intolerance episode, was calculated in the subpopulation. The RR ratio for feeding intolerance, defined as interruption of enteral feeding for at least eight consecutive hours during the observation period, was found to be 0.40 in the D-HMF group, equal to that reported in the main clinical trial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 reports the main clinical outcomes following ADJ fortification in the two groups. The relative risk (RR) ratio for the primary outcome of the original clinical study [18], i.e., the occurrence of at least one feeding intolerance episode, was calculated in the subpopulation. The RR ratio for feeding intolerance, defined as interruption of enteral feeding for at least eight consecutive hours during the observation period, was found to be 0.40 in the D-HMF group, equal to that reported in the main clinical trial.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have shown that preterm and VLBW infants receiving isocaloric and isoproteic supplementation of HM with either bovine milk-based fortifier (B-HMF) or experimental donkey milk-based fortifiers (D-HMF) achieve similar auxological outcomes. Additionally, a donkey milk-based fortifier significantly reduced the occurrence of feeding intolerance, feeding interruptions, bilious gastric residuals and vomiting [18]. As an extension of our previous study, the current investigation aims at applying the metabolomics approach to explore the modulation of the two above-mentioned fortifiers on the metabolic phenotype of preterm infants after a 21-day period of adjustable (ADJ) fortification.…”
Section: Introductionmentioning
confidence: 96%
“…Median value for bradycardia was 67 (63-78) beats per minute with a lowest of 58 beats per minute. The median duration of apnea events was 12 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) seconds, the longest apnea recorded was 38 seconds long. Detailed CR monitoring data are reported in Table 3.…”
Section: Resultsmentioning
confidence: 97%
“…This study suggests that DF improves feeding tolerance when compared with standard BF showing a lower number of failures (necrotizing enterocolitis, FI, death) and lower risk of FI episodes. (14) The evaluation of GER and gastric emptying, as a marker of FI, was evaluated by multichannel intraluminal impedance and pH monitoring (MII/pH) and gastric ultrasound (US) as secondary endpoints of the FortiLat trial. (14,15) Aim of this study is to evaluate the effects of the DF on VLBW and very preterm infants enrolled in the FortiLat trial with symptoms of GER and CR events.…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional similarities with human milk, the gold standard for infant feeding, are also encouraging for other uses in children diet. Recently, a fortifier derived from donkey milk for preterm infants (which have suboptimal actual protein intake from breast milk) has been developed [3].…”
mentioning
confidence: 99%